Modulation of MAPK and NF-κB Signaling Pathways by Antioxidant Therapy in Skeletal Muscle of Heart Failure Rats - Martinez, Paula F. [UNESP]; Bonomo, Camila [UNESP]; Guizoni, Daniele M. [UNESP]; Oliveira, Silvio A. [UNESP]; Damatto, Ricardo L. [UNESP]; Cezar, Marcelo D.M. [UNESP]; Lima, Aline R.R. [UNESP]; Pagan, Luana U. [UNESP]; Seiva, Fabio R.; Bueno, Renata T. [UNESP]; Fernandes, Denise C.; Laurindo, Francisco R.; et al. (Karger Publishers, 2016)
Background/Aims: Although increased oxidative stress plays a role in heart failure (HF)-induced skeletal myopathy, signaling pathways involved in muscle changes and the role of antioxidant agents have been poorly addressed. We evaluated the effects of N-acetylcysteine (NAC) on intracellular signaling pathways potentially modulated by oxidative stress in soleus muscle from HF rats. Methods and Results: Four months after surgery, rats were assigned to Sham, myocardial infarction (MI)-C (without treatment), and MI-NAC (treated with N-acetylcysteine) groups. Two months later, echocardiogram showed left ventricular dysfunction in MI-C; NAC attenuated diastolic dysfunction. Oxidative stress was evaluated in serum and soleus muscle; malondialdehyde was higher in MI-C than Sham and did not differ between MI-C and MI-NAC. Oxidized glutathione concentration in soleus muscle was similar in Sham and MI-C, and lower in MI-NAC than MI-C (Sham 0.168 ± 0.056; MI-C 0.223 ± 0.073; MI-NAC 0.136 ± 0.023 nmol/mg tissue; p = 0.014). Western blot showed increased p-JNK and decreased p38, ERK1/2, and p-ERK1/2 in infarcted rats. NAC restored ERK1/2. NF-κB p65 subunit was reduced; p-Ser276 in p65 and IκB was increased; and p-Ser536 unchanged in MI-C compared to Sham. NAC did not modify NF-κB p65 subunit, but decreased p-Ser276 and p-Ser536. Conclusion: N-acetylcysteine modulates MAPK and NF-κB signaling pathways in soleus muscle of HF rats.
Keywords: Cardiac failure; Intracellular signaling; Myocardial infarction; Myopathy; Oxidative stress; Skeletal muscle